An original class of small sized molecules as versatile fluorescent probes for cellular imaging. Issue 54 (18th June 2019) - Sirbu, Doina; Diharce, Julien; Martinić, Ivana; Chopin, Nicolas; Eliseeva, Svetlana V.; Guillaumet, Gérald; Petoud, Stéphane; Bonnet, Pascal; Suzenet, Franck
Abstract : An unusual class, compact in sizes, of fluorescent probes based on pyridazino-1, 3 a, 6 a -triazapentalene scaffolds exhibits promising fluorescent properties with good solubility and good photostability suitable for optical imaging applications. Abstract : An unusual class, compact in size, of fluorescent probes based on pyridazino-1, 3 a, 6 a -triazapentalene scaffolds exhibits promising fluorescent properties (quantum yield values up to 73%, large Stokes shifts, emission wavelengths located in the green-yellow range, excellent solubility) with good photostability suitable for optical imaging applications.